2013
DOI: 10.3928/00989134-20130403-01
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Testing a Couples-Focused Intervention for Mild Cognitive Impairment

Abstract: The purpose of this pilot study was to evaluate the acceptability, feasibility, and potential benefits of the multi-component Daily Enhancement of Meaningful Activity (DEMA) intervention, which was tailored to help couples facing mild cognitive impairment (MCI) work together to meet goals, remain engaged in meaningful activities, and adapt to changes over time. Using a single-group design, 10 persons with MCI and their family caregivers were recruited to receive DEMA over six bi-weekly sessions. Data were coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…IDF recommended WC as the most frequently used anthropometric index to define abdominal obesity [6]. Paradoxically, WC, BP, lipid, and glucose levels were similar among men and women in this study as reported in the same general population [10]. However, WC cutoff points differ by ethnic groups and gender worldwide [1,4].…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…IDF recommended WC as the most frequently used anthropometric index to define abdominal obesity [6]. Paradoxically, WC, BP, lipid, and glucose levels were similar among men and women in this study as reported in the same general population [10]. However, WC cutoff points differ by ethnic groups and gender worldwide [1,4].…”
Section: Discussionmentioning
confidence: 51%
“…Contrary to the previous myths, non communicable diseases (Diabetes, hypertension, MS, atherosclerosis) are no longer rare in Africa [10-14]. The extent is increasing and it is thought to be due to the shifting from traditional African customs to the Western lifestyle [15-18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The DEMA conceptual framework (Figure 1) was developed based on: gerontological theory (Lawton, 1990), the Model of Human Occupation (Kielhofner, 2002), components of Problem-Solving Therapy (PST) (Unützer et al, 2002), and findings from two phenomenology studies of patients living with MCI and their caregivers and a three-phase DEMA intervention development study (Lu & Haase, 2009; Lu, Haase, & Farran, 2007; Lu, Haase, & Weaver, 2013). Based on the framework, the DEMA intervention has several features.…”
Section: Introductionmentioning
confidence: 99%
“…DEMA is described in detail in another publication by Lu and her colleagues (2013). DEMA was tailored to patient and caregiver congruence in level of awareness of functional ability and to their types and frequencies of meaningful activity and perceived barriers to engaging in these activites.…”
Section: Introductionmentioning
confidence: 99%